«Химиялық кинетика» бөлімінің әр түрлі тапсырмаларын мектептегі химия курсында қолдану - alkhambetova, aidana (Вестник ЗКУ, 2023)
The use of various tasks in the section "chemical kinetics" in the school chemistry courseUssipbekova Ye.Zh., Alhambetova A., Torebai A.N.         Annotation. The study of the kinetics of any chemical processes allows you to deeply understand their mechanism.  The performance of various technological processes, the type and size of installations used in them, the effect of certain chemical or biotechnological processes, fertilizers and medicines on living organisms, and many other phenomena depend on the rate of chemical reactions.  Therefore, it is very important to teach future chemists the kinetic foundations of any chemical processes, starting from the school course.  However, this topic is not fully disclosed in the school course.  There is no doubt that teaching students the rate of a chemical reaction, the factors affecting it (temperature, concentration, catalyst), methods for determining it, as well as the use of various methods is an effective method to improve the quality of schoolchildren's education and the training of future specialists.  Keywords: kinetics, reaction rate, rate constant, temperature, concentration, activation energy.  Использование различных задачи по разделу «химическая кинетика» в школьном курсе химииУсипбекова Е.Ж., Алхамбетова А., Торебай А.Н. Аннотация.Изучение кинетики любых химических процессов позволяет глубоко понять их механизм. От скорости химических реакций зависят производительность различных технологических процессов, тип и размеры используемых в них установок, действие некоторых химических или биотехнологических процессов, удобрений и лекарственных средств на живые организмы и многие другие явления. Поэтому очень важно обучать будущих специалистов-химиков кинетическим основам любых химических процессов, начиная со школьного курса. Однако в школьном курсе эта тема раскрыта не полностью. Бесспорно, что обучение студентов скорости химической реакции, факторам, влияющим на нее (температура, концентрация, катализатор), методам ее определения, а также использованию различных методов является эффективным методом для повышения качества обучения школьников и подготовки будущих специалистов.  Ключевые слова: кинетика, скорость реакции, константа скорости, температура, концентрация, энергия активации.